Structural, morphological and electrochemical studies of nanostructured BiVO4 for supercapacitor application. (15th August 2020) - Packiaraj, R.; Venkatesh, K.S.; Devendran, P.; Bahadur, S. Asath; Nallamuthu, N.
Abstract: A facile and cost-effective stratagem has been applied in the synthesizing of multifunctional Bismuth Vanadate (BiVO4 ) nanoparticles (NPs) by using one-step hydrothermal method. The synthesized BiVO4 NPs under three different temperatures such as 140, 160 and 180 °C led different morphologies. Further they have been subjected to various characterizations such as XRD, FTIR, SEM, RAMAN, UV and electrochemical analyses. XRD pattern showed the combined monoclinic and tetragonal crystal structures which may be due to various temperatures (140, 160 and 180 °C). FTIR is proved with metal oxide (V–O) vibrations and also substantiated the purity of the samples. The optical band gap values were studied by UV spectral results for different reaction temperatures. The electrochemical evaluation and supercapattery studies were carried out for all the samples. The maximum specific capacitance (Csp ) of 1451 F g −1 at a current density of 1 A g -1 was observed to BiVO4 NPs synthesized at 180 °C. Graphical abstract: Image 1 Highlights: Preparation of BiVO4 nanoparticles (NPs) with three different shapes via hydrothermal method. It utilizes as electrode materials for pseudocapacitors (PCs) supercapacitors application. Synthesized materials exhibit good crystalline nature of tetragonal monoclinic and pure monoclinic BiVO4 . A high specific capacitance of 1451 F g −1 at current density of 1 A g −1 is achieved. The developed electrode exhibited 97.4% retention efficiency up to 5000 cycles.